2011
DOI: 10.1097/nrl.0b013e3181f4ec88
|View full text |Cite
|
Sign up to set email alerts
|

Newly Suggested Surgical Method of Decompressive Craniectomy for Patients With Middle Cerebral Artery Infarction

Abstract: Objectives:The purpose of this study is to suggest the landmarks for decompressive craniectomy so that surgery can be standardized to achieve adequate decompression in patients with malignant middle cerebral artery infarction. We also analyzed the efficacy and safety of this newly suggested surgical method. Methods:Eleven patients (group A) underwent this newly suggested decompressive surgery. The bony landmarks for decompressive craniectomy are described. The area of the bone flap and the brain volume protrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Furthermore, perioperative blood loss, postoperative infections, duration of intubation and time to rehabilitation did not differ between groups, which is in line with a previous report on 60 patients who were treated with sDHC in 2001 and a recent publication from 2011 on 25 patients with large craniectomies, where surgical revision was necessary in only 1 patient because of an epidural hematoma [12,28] . In contrast to our protocol, however, in both these studies, DHC was performed as a rescue treatment at a time when signs of herniation were already present.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, perioperative blood loss, postoperative infections, duration of intubation and time to rehabilitation did not differ between groups, which is in line with a previous report on 60 patients who were treated with sDHC in 2001 and a recent publication from 2011 on 25 patients with large craniectomies, where surgical revision was necessary in only 1 patient because of an epidural hematoma [12,28] . In contrast to our protocol, however, in both these studies, DHC was performed as a rescue treatment at a time when signs of herniation were already present.…”
Section: Discussionsupporting
confidence: 88%
“…More than the technique of DHC, the dimensions of the removed bone flap are considered crucial, since they define the amount of additionally created volume for the swollen brain to occupy [10][11][12][13][14]. Using mathematical formulas, this volume can be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, these results are supported by a prospective study of Kilincer et al identifying sings of herniation as a prognostic factor for poor outcome [31], and by several retrospective trials [32,33,34]. Furthermore, in the studies of Skoglund et al (n = 18) and Chung et al (n = 24) 67 and 100% of patients, respectively, showed signs of herniation, leading to worse neurological outcomes compared to the results of the DECIMAL and DESTINY trials [8,9,35,36]. …”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In a recently published study, Chung et al could demonstrate that a maximal size of decompression craniectomy (>14-16 cm or >399 cm 2 ) versus a large size (>12 cm or 308 cm 2 ) increases the ratio of a favorable outcome 3 months after stroke (mRS ≤3) and decreases the ratio of poor outcomes or deceased patients [36]. …”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Decompressive craniectomy (DC) is an important method to decreased ICP,9) and DC is widely performed throughout the world 10). This surgical procedure is performed by any neurosurgeons or even residents under training, so it should achieve enough decompression without interoperator differences, but textbook only commented that "the bone flap should not be just as large as possible" 3). The authors considered that the skin incision could interfere the size of enough decompression area, and considered new skin incision technique what we called the "n-shaped skin incision".…”
Section: Introductionmentioning
confidence: 99%